Computer-tomography features of hemodynamics in hepatocellular carcinoma foci depend on the stage of histological differentiation - U. N. Tumanova; N. I. Yashina; Ye. A. Dubova; G. G. Karmazanovsky; A. I. Schegolev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To define computer-tomography (CT) densitometry features of hepatocellular carcinoma (HCC) at different stages of histological differentiation and to correlate CT vascularisation degree to morphological features.Material and methods. The study was based on the clinical and morphological data of 19 patients (12 men and 7 women, aged 18–72 years), with hepatocellular carcinoma (HCC) without coexistent liver cirrhosis. At a preoperative stage all patients underwent helical CT with bolus contrast enhancement (four phases study), with estimation of arterial and venous density gain ofthe lesion and CT-vascularization index. The morphometric analysis of HCC blood vessels was carried out in immunehistochemical specimens stained for CD34 and CD105.Results. According to CT and immunohistochemistry data highly differentiated carcinomas were the most vascularized (hypervascular), while poorly differentiated HCC were the least vascularized. Hemodynamic functionality in moderately-differentiated tumor nodes was significantly higher as compared to well differentiated tumor. The poorly differentiated tumor was characterized by decrease in both total number of blood vessels, and the quantity of neovasculatures that underlies transition of cells to anaerobic way of metabolism.Conclusion. Decrease in histological differentiation grade and concomitant gain of malignant potential of neoplasm is associated to reduction of the total area ofbarterial blood vessels. Computer tomography scores should be applied as additional criteria of the tumor malignant potential and for estimation of treatment efficacy as well.